Achieving economic and environmental sustainability with supply chain contracts - Dong, Chuanwen (2025)
How to decarbonize transportation, which is now, unfortunately, the largest source of carbon emissions among all sectors? The entire industry is heavily driven by economies of scale. When more freight is collected in a lane, it can be shifted to a greener transport mode (e.g., from less-than-truckload to full-truckload, and further to rail transport), and costs and emissions are saved. To support firms achieving such benefits, we develop novel supply chain contracting models that capture supply chain partners’ strategic orders, as well as freight transportation modes with trade-offs on costs, emissions, and flexibility (in the form of a minimum transport quantity for the green mode). We find that even a conventional price-only contract with an option to shift freight mode can already boost the use of the green transport mode and considerably improve supply chain efficiency. Furthermore, we design a revenue-sharing contract that can incentivize even larger order quantities from the retailer and strongly promote the use of the green transport mode. We characterize the conditions under which the contract can achieve a win–win situation, that is, increasing economic as well as environmental sustainability of the supply chain. In a follow-up case study using realistic industry-level data, we numerically evaluate how the supply chain parameters affect this win–win situation.